Cognitive mediation for student permanence at university with sensory disabilities - Miranda, Washington Rafael; González de Pirela, Nelia (Omnia, 2025)
When studying cognitive mediation by teachers for the permanence of students with sensory disabilities at the State University of Milagro, it is seen that, at a global level, these people face significant inequalities. In Ecuador as a Latin American country, according to statistics from the National Council for Disability (CONADIS), the rates of educational exclusion are alarming. The general objective of the research was to design cognitive mediation strategies that favor the permanence of students in the Basic Education career, online modality, during the period 2024-2025. The methodology that is intended to be developed will be projective, with quantitative techniques and instruments with a non-experimental design, using surveys directed to 80 teachers and 29 students with sensory disabilities. The questionnaire will evaluate both the cognitive mediation of teachers and the permanence of students, allowing to identify the strategies that teachers use in the virtual environment. The results of the study are expected to offer a theoretical-practical framework that improves inclusive university educational policies, guaranteeing the permanence and academic success of students with sensory disabilities.